On the Nature of the Partial Covalent Bond between Noble Gas Elements and Noble Metal Atoms - Ranita Pal; Pratim Kumar Chattaraj (Molecules, 2023)
This article provides a discussion on the nature of bonding between noble gases (Ng) and noble metals (M) from a quantum chemical perspective by investigating compounds such as NgMY (Y=CN, O, NO3, SO4, CO3), [NgM−(bipy)]+, NgMCCH, and MCCNgH complexes, where M=Cu, Ag, Au and Ng=Kr−Rn, with some complexes containing the lighter noble gas atoms as well. Despite having very low chemical reactivity, noble gases have been observed to form weak bonds with noble metals such as copper, gold, and silver. In this study, we explore the factors that contribute to this unusual bonding behavior, including the electronic structure of the atoms involved and the geometric configuration of the concerned fragments. We also investigate the metastable nature of the resulting complexes by studying the energetics of their possible dissociation and internal isomerization channels. The noble gas-binding ability of the bare metal cyanides are higher than most of their bromide counterparts, with CuCN and AgCN showing higher affinity than their chloride analogues as well. In contrast, the oxides seem to have lower binding power than their corresponding halides. In the oxide and the bipyridyl complexes, the Ng-binding ability follows the order Au > Cu > Ag. The dissociation energies calculated, considering the zero-point energy correction for possible dissociation channels, increase as we move down the noble gas group. The bond between the noble gases and the noble metals in the complexes are found to have comparable weightage of orbital and electrostatic interactions, suggestive of a partial covalent nature. The same is validated from the topological analysis of electron density.